Adenovirus vector-based vaccines as forefront approaches in fighting the battle against flaviviruses. Issue 5 (30th November 2022) - Shoushtari, Mohammad; Roohvand, Farzin; Salehi-Vaziri, Mostafa; Arashkia, Arash; Bakhshi, Hasan; Azadmanesh, Kayhan
ABSTRACT: Flaviviruses are arthropod-borne viruses (arboviruses) that have been recently considered among the significant public health problems in defined geographical regions. In this line, there have been vaccines approved for some flaviviruses including dengue virus (DENV), Japanese encephalitis virus (JEV), yellow fever virus (YFV), and tick-borne encephalitis virus (TBEV), although the efficiency of such vaccines thought to be questionable. Surprisingly, there are no effective vaccine for many other hazardous flaviviruses, including West Nile and Zika viruses. Furthermore, in spite of approved vaccines for some flaviviruses, for example DENV, alternative prophylactic vaccines seem to be still needed for the protection of a broader population, and it originates from the unsatisfying safety, and the efficacy of vaccines that have been introduced. Thus, adenovirus vector-based vaccine candidates are suggested to be effective, safe, and reliable. Interestingly, recent widespread use of adenovirus vector-based vaccines for the COVID-19 pandemic have highlighted the importance and feasibility of their widespread application. In this review, the applicability of adenovirus vector-based vaccines, as promising approaches to harness the diseases caused by Flaviviruses, is discussed.